A universal cannabinoid CB1 and CB2 receptor TR-FRET kinetic ligand-binding assay - Borrega-Roman, Leire; Hoare, Bradley L.; Kosar, Miroslav; Sarott, Roman C.; Patej, Kacper J.; Bouma, Jara; Scott-Dennis, Morgan; Koers, Eline J.; Gazzi, Thais; Mach, Leonard; Barrondo, Sergio; Sallés, Joan; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe kinetics of ligand binding to G protein-coupled receptors (GPCRs) is an important optimization parameter in drug discovery. Traditional radioligand assays are labor-intensive, preventing their application at the early stages of drug discovery. Fluorescence-based assays offer several advantages, including a possibility to develop a homogeneous format, continuous data collection, and higher throughput. This study sought to develop a fluorescence-based binding assay to investigate ligand-binding kinetics at human cannabinoid type 1 and 2 receptors (CB1R and CB2R).MethodsWe synthesized D77, a novel tracer derived from the non-selective cannabinoid Δ8-THC. Using time-resolved Förster resonance energy transfer (TR-FRET), we developed an assay to study ligand-binding kinetics at physiological temperatures. For CB1R, we truncated the first 90 amino acids of its flexible N-terminal domain to reduce the FRET distance between the terbium cryptate (donor) and the fluorescent ligand (acceptor). The full-length CB2R construct was functional without modification due to its shorter N-terminus. The Motulsky–Mahan competition binding model was used to analyze the binding kinetics of the endocannabinoids and several other non-fluorescent ligands.ResultsThe D77 tracer showed nanomolar-range affinity for truncated CB1R (CB1R91-472) and full-length CB2R (CB2R1–360), displaying competitive binding with orthosteric ligands. D77 exhibited rapid dissociation kinetics from both CB1R and CB2R, which were similar to the fastest dissociating reference compounds. This was critical for accurately determining the on- and off-rates of the fastest dissociating compounds. Using D77, we measured the kinetic binding properties of various CB1R and CB2R agonists and antagonists at physiological temperature and sodium ion concentration.DiscussionThe kon values for molecules binding to CB1R varied by three orders of magnitude, from the slowest (HU308) to the fastest (rimonabant). A strong correlation between kon and affinity was observed for compounds binding to CB1R, indicating that the association rate primarily determines their affinity for CB1R. Unlike CB1R, a stronger correlation was found between the dissociation rate constant koff and the affinity for CB2R, suggesting that both kon and koff dictate the overall affinity for CB2R. Exploring the kinetic parameters of cannabinoid drug candidates could help drug development programs targeting these receptors.